Redistribuição de nutrientes em folhas de pinhão-manso entre estádios fenológicos - Lima, Rosiane. L. S. de; Severino, Liv S.; Cazetta, Jairo O. [UNESP]; Azevedo, Carlos A. V. de; Sofiatti, Valdinei; Arriel, Nair H. C. (Universidade Federal da Paraíba (UFPB) Ccsa, 2011)
Nutrient redistribution from mature leaves to growing structures is an important process in plant physiology. Each nutrient is redistributed in a different rate and time. This study aimed to quantify redistribution of macronutriens and minor nutrients in Jatropha curcas leaves through five phenological phases (expanding leaf, young leaf, mature leaf, senescing leaf, and dry leaf). It was observed that the nutrients P, K, Cu, and Zn are intensively redistributed from older to younger jatropha leaves, while N, Ca, Mg, Fe, and Mn are poorly redistributed. Leaf senescence causes a loss of the nutrients that are not redistributed because they will need to be re-absorbed for supporting the growth of new structures in the plant.
Redistribution of nutrients in jatropha leaves through phenological phases
Keywords: Jatropha curcas; nutrients translocation; Nutrition